Simplification Strategies to Reduce Antiretroviral Drug Exposure: Progress and Prospects - McKinnon, John E. (2009)
Current US guidelines for initial therapy of HIV-1 infection recommend daily, life-long treatment with a combination of three antiretroviral drugs consisting of two nucleoside analog reverse transcriptase (RT) inhibitors and a nonnucleoside RT inhibitor or a protease inhibitor. Although this approach has been successful in reducing morbidity and mortality from HIV-1 infection, concerns remain about adverse events from chronic drug exposure, the requirement for daily medication adherence, the risk of HIV-1 drug resistance, and high treatment costs. The availability of antiretrovirals that are co-formulated and dosed once-daily have reduced pill burden and have simplified dosing schedules, but have not lowered drug exposure or cost. These limitations have stimulated research into drug-sparing strategies including intermittent therapy and simplified maintenance regimens. Randomized clinical trials have shown greater mortality with intermittent therapy compared with continuous therapy leading to rejection of this strategy. Pilot studies of simplified maintenance therapy with a ritonavir-boosted protease inhibitor alone have shown more promise, although concerns remain. This article reviews progress in simplification of antiretroviral therapy, recent clinical trial results, and prospects for the future.